Dutch Migrants in New Zealand: Did they Fare Well? - Joop Hartog; Rainer Winkelmann (Institute for the Study of Labor (IZA), 2000)
We analyse postwar Dutch migration to New Zealand. We document that history, reflect on analytical and econometric modelling and then combine a sample of Dutch migrants in New Zealand with a representative sample of Dutch in The Netherlands to estimate wage equations simultaneously with the migration decision. We use the results for ex post evaluation of the migration decision.
Keywords: F22; J61; 330; Dutch emigration; New Zealand immigration; labour market self-selection; Migranten; Niederländisch; Arbeitsmarkt; Lohnniveau; Neuseeland